The Impact of Early Neighborhood Cohesion, and Its Mechanism, on Cognitive Function in Later Life - Zhou, Tao; Zhang, Xiaoyi; Fan, Shuming; Deng, Zeming; Jiao, Can (Frontiers in Psychiatry, 2022)
Objectives: This study aimed to explore the impact of early neighborhood cohesion on cognitive function in later life and its mechanism. Methods: 10727 Chinese elderly aged 60-90 in the two waves of data (2014 and 2018) from the China Health and Retirement Longitudinal Study (CHARLS) were used as a sample. MMSE, LHSQ and CESD-10 were used to assess the neighborhood cohesion and cognitive function of the elderly. We used the structural equation model to examine the relationship between early neighborhood cohesion and late-life cognitive function and conducted bootstrapping analyses to test their mechanism. Results: Childhood neighborhood cohesion not only has a direct effect on cognitive function (β = 0.31，p ＜ 0.001), but also positively predicted cognitive function of the elderly through the mediating effect of childhood friendship, and this mediating effect includes depression and social activity participation two chain paths. Conclusions: Findings suggest that Childhood neighborhood cohesion positively predicts the cognitive function among elderly people through the mediating role of childhood friendship, depression, and social activities engagement. Childhood neighborhood cohesion is related to better childhood friendship, then to fewer depression symptoms and more elderly social activity participation, and finally to better cognitive function in the elderly.